The political clan in Calbiga its extent of influence to the voting behavior of the constituents - Cabuello, Clariza D.; Oreo, Cristina D. (1997)
Calbiga, W. Samar is a municipality of the second district of the province, performs certain government function, the election. It is a process of changing local leadership and this usually takes place every three years. In this leadership selection, it is participated by able individuals who will lead the municipalities in such a way that the constituents can avail of the benefits that national government has slated for them.
In the said municipality there is the existence of political clan that oftentimes participates in the political process. The handling of local chief executive position can be traced to the Figueroas and the local executive power always reside in their hands.
Their end in politics is undetermined. The generations of their blood always go along with politics and up to the present there is still a high regard for them. Precisely, this clan is enjoying such a thing and they are very much motivated for a certain government position particularly as local chief executive. It is a fact that a career in government or politics is viewed as a family opportunity for wealth and lifetime security.
Undergraduate thesis (B.A.S.S. Political Science)-- University of the Philippines, Tacloban.
Keywords: Political clan -- Philippines -- Calbiga (W.Samar).